Responses of Organisms to Water Stress - Akıncı, Sener (IntechOpen, 2013)
The same amount of water has been present on our planet for about 4 billion years, since shortly after the Earth was formed. Since then it has cycled through evaporation, condensation, precipitation and surface runoff multiple times. Water scarcity as an abiotic factor ranging from moderate to severe stress levels, accompanied by loss of moisture in the soil, is extremely hard for most organisms to cope with, particularly terrestrial plants and their food-chain dependents. Because of the potential for increasing temporary, or posssibly permanent, drought conditions in the future, there is intense focus on improving plant resistance to drought and increasing yield performance in water- limited environments through genotype selection in important crops. This book aims to contribute to understanding of how plants and other organisms respond to water stress conditions, and the various survival strategies adopted under differing moisture levels.